Supraphysiological doses of performance enhancing anabolic-androgenic steroids exert direct toxic effects on neuron-like cells - Basile, John R.; Binmadi, Nada O.; Zhou, Hua; Yang, Yinghua; Paoli, Antonio; Proia, Patrizia (Frontiers in Cellular Neuroscience, 2013)
Anabolic-androgenic steroids (AAS) are lipophilic hormones often taken in excessive quantities by athletes and bodybuilders to enhance performance and increase muscle mass. AAS exert well known toxic effects on specific cell and tissue types and organ systems. The attention that androgen abuse has received lately should be used as an opportunity to educate both athletes and the general population regarding their adverse effects. Among numerous commercially available steroid hormones, very few have been specifically tested for direct neurotoxicity. We evaluated the effects of supraphysiological doses of methandienone and 17-α-methyltestosterone on sympathetic-like neuron cells. Vitality and apoptotic effects were analyzed, and immunofluorescence staining and western blot performed. In this study, we demonstrate that exposure of supraphysiological doses of methandienone and 17-α-methyltestosterone are toxic to the neuron-like differentiated pheochromocytoma cell line PC12, as confirmed by toxicity on neurite networks responding to nerve growth factor and the modulation of the survival and apoptosis-related proteins ERK, caspase-3, poly (ADP-ribose) polymerase and heat-shock protein 90. We observe, in contrast to some previous reports but in accordance with others, expression of the androgen receptor (AR) in neuron-like cells, which when inhibited mitigated the toxic effects of AAS tested, suggesting that the AR could be binding these steroid hormones to induce genomic effects. We also note elevated transcription of neuritin in treated cells, a neurotropic factor likely expressed in an attempt to resist neurotoxicity. Taken together, these results demonstrate that supraphysiological exposure to the AAS methandienone and 17-α-methyltestosterone exert neurotoxic effects by an increase in the activity of the intrinsic apoptotic pathway and alterations in neurite networks.